Human Mast Cells From Adipose Tissue Target and Induce Apoptosis of Breast Cancer Cells - Plotkin, Jesse D.; Elias, Michael G.; Fereydouni, Mohammad; Daniels-Wells, Tracy R.; Dellinger, Anthony L.; Penichet, Manuel L.; Kepley, Christopher L. (Frontiers in Immunology, 2019)
Mast cells are important immune sentinels found in most tissue and widely recognized for their role as mediators of Type I hypersensitivity. However, they also secrete anti-cancer mediators such as tumor necrosis factor alpha and granulocyte-macrophage colony-stimulating factor. The purpose of this study was to investigate adipose tissue as a new source of mast cells in quantities that could be used to study mast cell biology focusing on their ability to bind to and kill breast cancer cells. We tested several cell culture media previously demonstrated to induce mast cell differentiation. We report here the generation of functional human mast cells from adipose tissue. The adipose-derived mast cells are phenotypically and functionally similar to connective tissue expressing tryptase, chymase, c-kit, and FcɛRI and capable of degranulating after cross-linking of FcɛRI. The adipose-derived mast cells, sensitized with anti-HER2/neu IgE antibodies with human constant regions (trastuzumab IgE and/or C6MH3-B1 IgE), bound to and released mast cell mediators, when incubated with HER2/neu-positive human breast cancer cells (SK-BR-3). Importantly, the HER2/neu IgE-sensitized adipose-derived mast cells induced breast cancer cell death through apoptosis. Breast cancer cell apoptosis was observed after the addition of cell-free supernatants containing mediators released from FcɛRI-challenged adipose-derived mast cells. Apoptosis was significantly reduced when tumor necrosis factor alpha blocking antibodies were added to the media. Adipose tissue represents a source of mast cells that could be used for multiple research purposes and potentially as a cell-mediated cancer immunotherapy through the expansion of autologous (or allogeneic) mast cells that can be targeted to tumors through IgE antibodies recognizing tumor specific antigens.